2006
DOI: 10.1590/s1677-54492006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Correção endovascular do aneurisma de artéria poplítea bilateral

Abstract: The first report of a successful endovascular repair of a popliteal artery aneurysm was described in 1994. Since then, few series with not many cases have been published. Next, the authors describe two cases of successful endovascular repair of bilateral popliteal artery aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
2
0
6
Order By: Relevance
“…Kauffman et al, 8 in two cases treated with the endovascular technique, reported occlusion in both cases, one at 3 and another at 11 months after the treatment; however, both of them had proper circulatory compensation, with no need of additional treatment. In Brazil, Medeiros et al 20 have recently reported endovascular treatment using Hemobanh and Viabanh ® in two patients with bilateral popliteal artery aneurysm, both with present distal pulses at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Kauffman et al, 8 in two cases treated with the endovascular technique, reported occlusion in both cases, one at 3 and another at 11 months after the treatment; however, both of them had proper circulatory compensation, with no need of additional treatment. In Brazil, Medeiros et al 20 have recently reported endovascular treatment using Hemobanh and Viabanh ® in two patients with bilateral popliteal artery aneurysm, both with present distal pulses at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…As endovascular techniques develop, new approaches to management of popliteal aneurysms are being studied, in the hope of achieving lower complication rates. 2,10,11 The objective of this study is to describe the last 5 years' experience of repairing PAAs at the vascular and endovascular surgery department of the Hospital das Clínicas de Ribeirão Preto, affiliated to the Universidade de São Paulo (Brazil). These patients were treated using either endovascular or conventional methods, according to criteria for indication that include anatomy and surgical risk.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha señalado que el 16% de la población de más de 55 años sufre de esta enfermedad (Medeiros & Gaspar, 2006). Actualmente, el tratamiento de las enfermedades vasculares periféricas es una de las áreas de la medicina con mayor expansión y existe hoy, además del tratamiento con cirugía vascular tradicional, la cirugía endovascular que a través de los stents y de la angioplastia, buscan mejorar el éxito del procedimiento.…”
Section: Introductionunclassified